Solo leveling. 8 - Ch'ugong; h-goon (Anime creator) (Ize Press, 2024)
"After his victory on Jeju Island, the top guilds are all clamoring to recruit Jinwoo Sung, the strongest S-rank hunter and the hero of Korea--a far cry from the hapless E-rank hunter he used to be. As exciting as each new development is, however, Jinwoo's eager to finally get some answers, so an invitation from the system to return to the double dungeon that changed his life is a welcome opportunity. He'll have to put the visit on the back burner, though, because first things first--Jinwoo has a guild to establish!"--Amazon.